PENDEKATAN-PENDEKATAN DALAM PENGEMBANGAN TARUSAN KAMANG MENJADI OBJEK WISATA DI KABUPATEN AGAM SUMATERA BARAT - Alfarisi, M. Salman; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aimed About Approaches Under Development Tarusan Kamang Become Attractions In Agam district of West Sumatra. This study aims to: (1) To determine the approach ever undertaken in the development of Tarusan Kamang become a tourist attraction. (2) To determine the most dominant approach undertaken in the development Tarusan Kamang become a tourist attraction.This study uses qualitative descriptive method to describe the problem in government agencies. The sample used in this study is 8 people.Based on the research that has been done, the result for the Development Approaches In Tarusan Kamang Become Attractions In Agam district of West Sumatra is pretty good. This is evidenced by the results of interviews with the acquisition of information in the field.Keywords : traditional and religious approaches , existing rule approach , a comprehensive approach , integrated approach , an environmentally sound approach , implemented approach , community approach .